ON THE TREATMENT OF CONCORDANT URANIUM-LEAD AGES - Ludwig K.R. (My University, 1998)
Uranium-lead analyses that yield arguably concordant U/Pb and Pb/Pb ages are highly reliable and often very precise; however, there is no generally accepted way for either assigning a best age and age-error or for evaluating assertions of concordance. Two general methods for these purposes, one for samples requiring only small common Pb corrections, the other for samples requiring large common Pb corrections, are given in this paper. Both the Concordia age (for radiogenic-Pb/U ratios) and the Total-Pb/U isochron (a three-dimensional isochron than includes 204Pb) obviate the often dubious practice of selecting a best parent-daughter ratio to use for a U/Pb or Pb/Pb age or isochron, make optimum use of both decay schemes, and accommodate errors in the U decay constants. In addition, the Total Pb/U isochron recovers the complete set of uranogenic Pb isotope ratios, errors, and error correlations in a single regression.